I feel like dancing : a year with Jacques D'Amboise and the National Dance Institute - Barboza, Steven; D'Amboise, Carolyn George (New York : Crown Publishers, 1992)
Describes, in text and illustrations, the experiences of three students during the year they spend as members of Jacques D'Amboise's National Dance Institute.
Faculty
Keywords: D'Amboise, Jacques, -- 1934- -- Juvenile literature; D'Amboise, Jacques, -- 1934-; National Dance Institute (U.S.) -- Juvenile literature; National Dance Institute (U.S.); Dance